CARDIOVASCULAR RISK ASSESSMENT AND SUPPORT TECHNIQUES: Whole blood viscosity assessment issues I: Extrapolation chart and reference values - Nwose, Ezekiel Uba (Medknow Publications & Media Pvt Ltd, 2010)
BACKGROUND: There are many different methods for the assessment of whole blood viscosity, but not every pathology unit has equipment for any of the methods. However, a validated arithmetic method exists whereby whole blood viscosity can be extrapolated from haematocrit and total serum proteins. AIMS: The objective of this work is to develop an algorithm in the form of a chart by which clinicians can easily extrapolate whole blood viscosity values in their consulting rooms or on the ward. Another objective is to suggest normal, subnormal and critical reference ranges applicable to this method. MATERIALS AND METHODS: Whole blood viscosity at high shear stress was determined, from various possible pairs of haematocrit and total proteins. A chart was formulated so that whole blood viscosity can be extrapolated. After determination of two standard deviations from the mean and ascertainment of symmetric distribution, normal and abnormal reference ranges were defined. RESULTS: The clinicians’ user-friendly chart is presented. Considering presumptive lower and upper limits, the continuum of ≤14.28, 14.29 – 15.00, 15.01 – 19.01, 19.02 – 19.39 and ≥19.40 (208 Sec(-1)) is obtained as reference ranges for critically low, subnormal low, normal, subnormal high and critically high whole blood viscosity levels respectively. CONCLUSION: This article advances a validated method to provide a user-friendly chart that would enable clinicians to assess whole blood viscosity for any patients who has results for full blood count and total proteins. It would make the assessment of whole blood viscosity costless and the neglect of a known cardiovascular risk factor less excusable.